Thai High Achieving Lecturers and Their Language Learning Strategies and Motivation: A Case Study of Kalasin University - Wilawan Tongsukkaeng (Journal of Educational Issues, 2024)
The purposes of this study were to (1) investigate the language learning strategies used for improving English language skill of the high achieving non-English major lecturers at Kalasin University and (2) investigate the motivation used for improving their English language skills. The sample comprised eight non-English major lecturers. They were purposively selected according to their high TOEIC test scores. Semi structured interview was used as a research tool. The interview was on using the language learning strategies and motivation to develop the English-speaking ability as the main instrument. The modified interview adapted from the Semi-Structured Interview Guide of Paredes (2010). The qualitative data were analyzed through using axial coding technique. The majors finding were as follows: (1) metacognitive, social and cognitive strategies were frequently used respectively by the sample, while compensation and memory strategies were least used equally and (2) the most motivations employed were attitude and competence motivation, the motivations moderately used were achievement, affiliation, and fear motivation equally, and the least motivation used were power and incentive motivation respectively.